Electromagnetic Radiation In Europe: Analysis of Standards And Their Importance For The Quality of Human Life - Sławomir RYBKA (Communications of International Proceedings, 2025)
The motivation for further research is the increasing prevalence of radiofrequency (EMF) coverage as a result of the development of wireless technologies and industrial services. Increasingly, human exposure to non-ionizing electromagnetic fields in the natural environment and conventional parenting, concerning effects, special in the context of immediate effects, is occurring. Presentation of the existence of findings, such as the application of ICNIRP, in a scientific publication, which is a gap in the scope of divergences in national standards on the use of EMF in Europe. There is also a lack of analysis of the use of methods to reduce exposure, especially in the conditions of ordinary life and work. Diverse Member States for prevention and comments on the extension of in-depth comparative analysis. In the article on the review-analytical application, after the application of the EMF emission standard in individual countries and explanation of their scientific basis and descriptions. Additional personal protective and protective measures, including fabrics and screening products, with a recent review of research on their detailed. Conclusions on important issues in national regulations and on their harmonization. Impact on the high potential of shielding technologies as a disruptive limiting effect on EMF. Effective health protection requires the use of consistent regulations as well as the use of evidence-based prevention.
Keywords: electromagnetic radiation; EMR exposure; health effects; European standards; legal regulations; occupational safety; wireless technologies; radiation protection; workplace exposure; EMR mitigation strategies; Risk Management